The Contagion Externality of a Superspreading Event: The Sturgis Motorcycle Rally and COVID-19 - Dhaval M. Dave; Andrew I. Friedson; Drew McNichols; Joseph J. Sabia (Institute of Labor Economics (IZA), 2020)
Large in-person gatherings without social distancing and with individuals who have traveled outside the local area are classified as the "highest risk" for COVID-19 spread by the Centers for Disease Control and Prevention (CDC). Between August 7 and August 16, 2020, nearly 500,000 motorcycle enthusiasts converged on Sturgis, South Dakota for its annual motorcycle rally. Large crowds, coupled with minimal mask-wearing and social distancing by attendees, raised concerns that this event could serve as a COVID-19 "super-spreader." This study is the first to explore the impact of this event on social distancing and the spread of COVID-19. First, using anonymized cell phone data from SafeGraph, Inc. we document that (i) smartphone pings from non-residents, and (ii) foot traffic at restaurants and bars, retail establishments, entertainment venues, hotels and campgrounds each rose substantially in the census block groups hosting Sturgis rally events. Stay-at-home behavior among local residents, as measured by median hours spent at home, fell. Second, using data from the Centers for Disease Control and Prevention (CDC) and a synthetic control approach, we show that by September 2, a month following the onset of the Rally, COVID-19 cases increased by approximately 6 to 7 cases per 1,000 population in its home county of Meade. Finally, difference-in-differences (dose response) estimates show that following the Sturgis event, counties that contributed the highest inflows of rally attendees experienced a 7.0 to 12.5 percent increase in COVID-19 cases relative to counties that did not contribute inflows. Descriptive evidence suggests these effects may be muted in states with stricter mitigation policies (i.e., restrictions on bar/restaurant openings, mask-wearing mandates). We conclude that the Sturgis Motorcycle Rally generated public health costs of approximately 12.2 billion.
Keywords: H75; I1; 330; large outdoor gathering; COVID-19; Sturgis Motorcycle Rally; social distancing